Design and Development of the RPG Game FORSAKEN Using a Visual and Narrative Approach in the Japanese Horror Genre - Hendriansyah, Muhammad Aditya; Geovanne Farell (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Forsaken is a Japanese horror RPG that combines visual, narrative, and gore elements to create an immersive gameplay experience. The story is set in a world abandoned by the gods due to human greed, with players taking on the role of a Ronin named Kairo who explores a cursed land known as the Land of Absolute Misery. The development of the game follows a pipeline method to ensure an efficient and structured workflow, utilizing RPG Maker MV as the main engine, along with Clip Studio Paint and Aseprite for visual asset creation. The aim of this project is to deliver a strong atmospheric and narrative representation of Japanese horror games while promoting indie game development through a distinct visual-narrative approach.